UNIMAS Outstanding Online Course Award, 2009 - Leaw, CP (Universiti Malaysia Sarawak (UNIMAS), 2009)
UNIMAS Outstanding Online Course Award, 2009 is coferred to Dr. Leaw Chui Pin in recognition of your outstanding use of Morpheus in supporting your teaching.